Influence of thermal radiation on magnetohydrodynamic (MHD) boundary layer flow of a viscous fluid over an exponentially stretching sheet - Idowu, Amos Sesan; Usman, S. (Zielona Góra: Uniwersytet Zielonogórski)
Radiation on a magnetohydrodynamic (MHD) boundary layer flow of a viscous fluid over an exponentially stretching sheet was considered together with its effects. The new technique of homotopy analysis method (nHAM) was used to obtain the convergent series expressions for velocity and temperature, where the governig system of partial differential equations was transformed into ordinary differential equations. The interpretation of these expressions is shown physically through graphs. We observed that the effects of the Prandtl and magnetic number act in opposite to each other on the temperature.
Keywords: boundary-layer; heat transfer; MHD; radiation; stretching sheet